Penerapan Prinsip Syariah dalam Manajemen Risiko Underwriting pada Asuransi Syariah di PT AIA Financial Indonesia Syariah - Fitriyani; Suryaman, Maman (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Sharia insurance is a financial instrument that is growing rapidly in Indonesia. So risk management is very important in sharia insurance due to several features of sharia insurance that differentiate it from conventional insurance, one of which is the principle of mutual assistance or tabarru', which requires sharia insurance companies to bear the risk if insurance participants experience a disaster. One of them is the insurance company at PT Finanacial Indonesia, Buah Batu branch, which is a Sharia Insurance Company that has been established for a long time. In this research, the researcher's aim is to find out how sharia principles are applied in PT AIA Financial Indonesia's underwriting risk management and the benefits of applying sharia principles in underwriting risk management at PT AIA Financial Indonesia. The method used by researchers in this research uses a qualitative descriptive method using data collection methods such as interviews and documentation. As for the data obtained using secondary data and primary data. The results of this research show that PT AIA Financial Indonesia has implemented sharia principles in underwriting risk management. These principles are fairness, balance and benefit, and are used in various underwriting policies and processes. For PT AIA Financial Indonesia, applying sharia principles in underwriting risk management has many advantages. These principles have helped companies manage risks in a fair and balanced manner, which has resulted in greater benefits for all parties.